The significance of high Ba basalts from the wilis volcanic complex, Sunda Arc A study for possible roles of sediment involvement in the magmatism - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Pengabdian Kepada Masyarakat UGM, 1998)
ABSTRACT Basalts from the Wilis volcano (or Wilis Volcanic Complex), Sunda Arc are characterized by high Ba concentrations and Ba/La ratios. Geochemical, including major and trace elements analyses were done using automated spectrometers (Phillips PW 41 D and PW 1980 X-Ray flourescences). Sr and Nd isotopic analyses also were done using the Finnigan MAT 261 mass spectrometer. The Sr and Nd fractions were separated using ion exchange method. Combined these characteristics and other trace elements (Ce, Pb) abundances as well as the radiogenic isotopic signature suggests that Bariched materials, e.g. sediments, may involved in the magma source. However, because of low Ba/La ratios of the Indian Ocean sediments, bulk mixing between MORB source and the sediments is unlikely. Ba may have been transported by fluid phase from the subducted slab (including sediments) to the mantle wedge causes the high Ba and Ba/La ratios in the source of the Wilis magma.